The Mediating Effect of Change of Direction Speed in the Relationship between the Type of Sport and Reactive Agility in Elite Female Team-Sport Athletes. - Domaradzki, Jarosław; Popowczak, Marek; Zwierko, Teresa (Journal of Sports Science & Medicine, 2021)
The main aim of this study was to examine the mediating effect of the change of direction speed (CODs) on reactive agility (RA) in female players participating in different team sports (TS). In total, there were 31 elite female players from the Polish national basketball (n = 12, aged 24.98 ± 3.38) and handball (n = 19, aged 27.34 ± 4.68) teams participated in this study. Two experiments using the 'five-time shuttle run to gates' test with similar movement patterns were used to determine the players' RA and CODs. A simple mediation model was utilised to investigate the potential mediation role of CODs and its effect on RA. The results revealed a primary, statistically significant effect of TS on RA (B = 0.796, p = 0.005), which decreased and became statistically insignificant after including the CODs variable into the model of mediation analysis (B = 0.337, p = 0.192). The RA test results were mediated by changes in CODs (B = 0.764, p < 0.001). Likewise, TS affected CODs (B = 0.602, p = 0.016). The general conclusion is that the relationship between TS and RA is not inherent. The direct effect of TS on RA disappears in the presence of the mediator CODs. Study results confirm the relevance of using the mediation analysis to apply in sport training. Identification of the critical ingredients of the athletes' agility performance can improve training programs by focusing on effective components.